Pelatihan dan Pendampingan Senam Menopause untuk Meningkatkan Kualitas Tidur pada Wanita Perimenopause di PMB Rama Agustina - Novi Rida Eriyani; Deby Meitia Sandy (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Perimenopausal women often experience sleep disturbances due to hormonal changes, which can negatively affect their physical health, psychological well-being, and quality of life. One non-pharmacological approach that can be used to address this problem is menopause exercise. This community service program aimed to improve the sleep quality of perimenopausal women through training and mentoring on menopause exercise at Rama Agustina Independent Midwifery Practice. The program consisted of health education, menopause exercise training, and exercise mentoring conducted three times per week for four weeks. Evaluation was carried out using pretest and posttest assessments of participants’ knowledge and sleep quality measurements using the Pittsburgh Sleep Quality Index (PSQI). The results showed an improvement in participants’ knowledge regarding perimenopause and the benefits of menopause exercise, as well as an improvement in sleep quality after participating in the program. Participants were also able to perform menopause exercise independently and demonstrated high enthusiasm throughout the activities. Training and mentoring on menopause exercise are easy-to-implement, safe, and potentially sustainable promotive and preventive interventions to improve sleep quality and overall quality of life among perimenopausal women.